A NumeraçãoKarib no Alto Xingu - Pedro Paulo Scandiuzzi (Revista Latinoamericana de Etnomatemática, 2008)
This article show us a history of numeration about indigenous matipu, kuikuro, ikpeng, Nahuquá and kalapalo, all speak karib linguistic family and all live in Xingu National Park, State of Mato Grosso, Brazil, area limited for Federal Government where live another 17 peoples indigenous speakers language the different linguistics family. The history went building beginning by dates of anthropological literature and trip writers and ethnography work did by author. The author put a numeration history listened for kuikuro indigenous and do little reflexions with eyes forward for Brazilian Mathematics History. Show also, reflexion about meeting their with national scholar system.